Comparative phylogenomic analyses and co-expression gene network reveal insights in flowering time and aborted meiosis in woody bamboo, Bambusa oldhamii ‘Xia Zao’ ZSX - Zhao, Wanqi; Guo, Chunce; Yao, Wenjing; Zhang, Li; Ding, Yulong; Yang, Zhenzhen; Lin, Shuyan (Frontiers in Plant Science, 2022)
Woody bamboos have peculiar flowering characteristics with intervals ranging from several years to more than 100 years. Elucidating flowering time and reproductive development in bamboo could be beneficial for both humans and wildlife. To identity the mechanisms responsible for flowering time and embryo abortion in Bambusa oldhami ‘Xia Zao’ ZSX, a transcriptome sequencing project was initiated to characterize the genes involved in developing flowers in this bamboo species. Morphological studies showed that pollen abortion in this bamboo species was mainly caused by a delay in tapetum degradation and abnormal meiotic process. Differential expression (DE) and optimized hierarchical clustering analyses identified three of nine gene expression clusters with decreasing expression at the meiosis of flowering stages. Together with enriched Gene Ontology Biological Process terms for meiosis, this suggests that their expression pattern may be associated with aborted meiosis in B. oldhami ‘Xia Zao’. Moreover, our large-scale phylogenomic analyses comparing meiosis-related transcripts of B. oldhami ‘Xia Zao’ with well annotated genes in 22 representative angiosperms and sequence evolution analyses reveal two core meiotic genes NO EXINE FORMATION 1 (NFE1) and PMS1 with nonsense mutations in their coding regions, likely providing another line of evidence supporting embryo abortion in B. oldhami ‘Xia Zao’. Similar analyses, however, reveal conserved sequence evolution in flowering pathways such as LEAFY (LFY) and FLOWERING LOCUS T (FT). Seventeen orthogroups associated with flowering were identified by DE analyses between nonflowering and flowering culm buds. Six regulators found primarily in several connected network nodes of the photoperiod pathway were confirmed by mapping to the flowering time network in rice, such as Heading date (Hd3a) and Rice FT-like 1 (RFT1) which integrate upstream signaling into the downstream effectors. This suggests the existence of an intact photoperiod pathway is likely the key regulators that switch on/off flowering in B. oldhami ‘Xia Zao’.